Regular postexercise sauna bathing does not improve heart rate variability: A multi‐arm randomized controlled trial - Earric Lee; Sascha Ketelhut; Petri Wiklund; Joel Kostensalo; Iiris Kolunsarka; Hans Hägglund; Juha P. Ahtiainen (Physiological Reports)
Abstract Regular exercise has been shown to increase heart rate variability (HRV) for different populations. Acute and short‐term studies using heat therapy and sauna bathing have also shown HRV improvements. However, long‐term adaptations in HRV to regular exercise and sauna bathing remain unexplored. In this 1:1:1 multi‐arm trial, sedentary participants (n = 38) aged 49 ± 9 years with at least one CVD risk factor were randomly assigned to regular exercise and 15‐min postexercise sauna (EXS), regular exercise only (EXE), or control (CON) group, for an 8‐week intervention. Indices of HRV (RR interval, RMSSD, SDNN, resting heart rate [HR], HRMAX–HRMIN, high frequency power [HFP], and low frequency power [LFP]) were measured before (PRE) and after (POST) the trial. Compared to CON, EXE increased the time‐domain measure of HRMAX–HRMIN (p = 0.003), and elicited significantly smaller decreases in the frequency‐domain measure of LFP (p = 0.022). There were no statistically significant differences between EXS and EXE for any of the HRV indices measured. Eight weeks of regular exercise conferred positive changes in both time‐ and frequency‐domain measures of HRV. However, adding regular sauna bathing postexercise offered no additional benefits to HRV over regular exercise alone.